Effect of NaCl and CaCl2 concentration on the rheological and structural characteristics of thermally-induced quinoa protein gels. (March 2022) - Yang, Zhi; de Campo, Liliana; Gilbert, Elliot Paul; Knott, Robert; Cheng, Lirong; Storer, Ben; Lin, Xiaoling; Luo, Lan; Patole, Shubham; Hemar, Yacine
Abstract: The effect of ionic strength on the heat-induced gelation of quinoa protein isolates (QPI) at pH 7 was investigated. The gelation behaviour and gel strength were characterised by oscillatory rheology. The microstructural characteristics of QPI solutions and gels were probed by ultra-small angle neutron scattering (USANS), small-angle X-ray and neutron scattering (SAXS, SANS), and confocal laser scanning microscopy (CLSM). This suite of techniques provided structural details covering a wide range of length scales from tens of micron to nanometre. It was found that the gelation temperature decreased from 73 °C to 40 °C and the G* (1 Hz) increased from ∼67 Pa to ∼1285 Pa with increasing concentration of NaCl from 0 to 200 mM. A particle size of ∼32 Å and ∼57 Å was identified within the QPI gel containing 0–200 mM NaCl from SAXS and SANS, respectively and whose size decreased upon addition of CaCl2 . For all QPI samples, heat treatment promoted protein aggregation on the micron scale, while a larger structural unit ( R g ∼ 170 nm) was kept intact as revealed by USANS. A similar mass fractal structure (df = 2) was observed in the QPI gels containing 0–200 mM NaCl, while CaCl2 addition caused the formation of large protein agglomerates ( R g ∼2.5–4.0 μm) with a more compact and denser structural organisation (df = 2.5) inside the protein blobs. CLSM showed that the QPI gels containing CaCl2 are prone to phase separation. Overall, this finding shows the thermal gelation behaviour of QPI can be modulated by the ion type and concentration, which is similarly observed in other globular protein systems. These results provide useful information for the design and preparation of quinoa gels for food applications. Graphical abstract: Ultra-small angle neutron scattering (USANS) patterns of thermal induced quinoa protein gels in the presence of 200 mM NaCl and 50 mM CaCl2 with confocal laser scanning micrographs inserted. Image 1 Highlights: Heat treatment promoted aggregation of quinoa protein to form a fractal-like network structure. Addition of NaCl (0–200 mM) led to an earlier onset of gelation and stronger gel strength. Addition of CaCl2 (20 and 50 mM) caused the formation of large micron scaled protein agglomerates and phase separation. USANS was firstly employed to investigate microstructures of thermally-induced plant protein gel.